2012
DOI: 10.5923/j.microbiology.20120202.05
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rhizosphere Bacteria for Control of Root Rot Disease and Improving Plant Growth of Wheat (<i>Triticum </i><i>a</i><i>estivum</i> L)

Abstract: Pathogenic fungus Rhizoctonia solani causes root rot disease in wheat leading to collapsing of the aerial part of the plant. To characterize antagonistic bacteria, one hundred and thirty bacterial isolates were obtained from the rhizosphere soil of wheat and these rhizobacterial isolates alongwith 72 reference strains were screened for their antagonistic interactions against R. solani under cultural conditions. Sixteen bacterial isolates inhibited the growth of R. solani and growth inhibition zone varied from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…These interactions could be beneficial, neutral or with detrimental effects (Walia et al, 2014). Some microbial populations in the rhizosphere termed as plant growthgrowth promoting rhizobacteria (PGPR) benefit the plant in a variety of ways, including: (i) increased recycling, solubilization and uptake of mineral nutrients such as nitrogen, phosphorus and potassium (Basak and Biswas, 2008;Sindhu et al, 2009;Parmar and Sindhu, 2013), (ii) synthesis of auxins, vitamins, amino acids and gibberlins (Lugtenberg and Kamilova, 2009;Jangu and Sindhu, 2011) and (iii) antagonism with potential plant pathogens by production of antibiotics, siderophores, hydrocyanic acid and/or hydrolytic enzymes (Weller, 2007;Dua and Sindhu, 2012). These different soil microorganisms possessing beneficial characteristics are used as bioinoculants to improve productivity of various crops in sustainable agriculture (Welbaum et al, 2004;Compant et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions could be beneficial, neutral or with detrimental effects (Walia et al, 2014). Some microbial populations in the rhizosphere termed as plant growthgrowth promoting rhizobacteria (PGPR) benefit the plant in a variety of ways, including: (i) increased recycling, solubilization and uptake of mineral nutrients such as nitrogen, phosphorus and potassium (Basak and Biswas, 2008;Sindhu et al, 2009;Parmar and Sindhu, 2013), (ii) synthesis of auxins, vitamins, amino acids and gibberlins (Lugtenberg and Kamilova, 2009;Jangu and Sindhu, 2011) and (iii) antagonism with potential plant pathogens by production of antibiotics, siderophores, hydrocyanic acid and/or hydrolytic enzymes (Weller, 2007;Dua and Sindhu, 2012). These different soil microorganisms possessing beneficial characteristics are used as bioinoculants to improve productivity of various crops in sustainable agriculture (Welbaum et al, 2004;Compant et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microbes have also been isolated and shown to be able to reduce Rhizoctonia disease on wheat (Barnett et al, 2006;Barnett et al, 2017;Broadbent et al, 1971;Dua and Sindhu, 2012;Mavrodi et al, 2012;Yin et al, 2013), and the potential for using biocontrol inoculants has been well documented (Berg, 2009;Dutta and Podile, 2010) with increasing social and economic drivers for the use of these agents (Bailey et al, 2010).…”
mentioning
confidence: 99%
“…Similar studies under similar conditions on soil bacteria and fungi have not been reported in Kenya. Dua and Sidhu [17]; Sood, et al [18] studied tea rhizosphere of Indian Himalayan regions for bacterial dominance and antagonism which indicated Bacillus bacteria of up to 45% occurrence and Pseudomonas of up to 85% occurrence to dominate the rhizosphere of established and abandoned tea bushes, respectively. In a study by Angel, et al [7]; Food and Agriculture Organization of the United Nations FAO [19] on isolation of siderosphore producing bacteria from rhizosphere soil and their antagonistic activity against selected fungal pathogens in Porur rhizosphere of tomatoes and paddy rice revealed the presence of eleven bacterial isolates which included, Fluorescent pseudomonas, Bacillus, Azobacter and non-fluorescent pseudomonas species.…”
mentioning
confidence: 99%
“…From a study by [7,17] on effectiveness of rhizosphere bacteria for control of root rot disease and improving plant growth of wheat (Triticum aestivum), antagonistic rhizosphere microbes which inhibit the growth of pathogenic microorganisms have been found to colonize the plant's rhizosphere. A study by Afzal, et al [2]; Deshmukh, et al [16] in India isolated the largest number of fungi from the rhizosphere soil of sugarcane.…”
mentioning
confidence: 99%